Novel hierarchical Ni/MgO catalyst for highly efficient CO methanation in a fluidized bed reactor. Issue 6 (6th January 2017) - Li, Jun; Zhu, Qingshan; Peng, Wencai; Zhang, Qiang; Luo, Guohua; Wei, Fei
Abstract : A facile synthesis of the hierarchical Ni/MgO catalyst is reported, with extremely fine dispersion of Ni nanoparticles (NPs) and high surface oxygen mobility. The hierarchical Ni/MgO catalyst exhibits higher activity for CH4 formation than that prepared by the impregnation method. The enhanced activity and thermal stability of the hierarchical Ni/MgO catalyst is attributed to hierarchical MgO particles with a multilayer structure and high surface oxygen mobility. This induces better metal‐support interactions, high Ni dispersion to prevent Ni NPs sintering, and the high surface oxygen mobility provides a high resistance to carbon deposition. Compared to the impregnated Ni/MgO catalyst, the hierarchical Ni/MgO catalyst exhibits a better fluidization quality and a higher attrition‐resistance in a fluidized‐bed reactor. This approach to improve the catalytic activity by creation of hierarchical Ni/MgO particles is encouraging for the design of novel catalysts for synthetic natural gas production, especially from the perspective of matching catalysts with fluidized‐bed reactors. © 2017 American Institute of Chemical Engineers AIChE J, 63: 2141–2152, 2017